Acute Effects Of Smoking On Blood Pressure And Heart Rate In Young Adults - Dias Costa, Joana (2023)
Introduction: Tobacco (Nicotiana tabacum) is a psychoactive plant, whose main chemical is nicotine, which is extremely addictive. Smokers have twice the risk of developing cardiovascular disease compared to non-smokers. At the level of the cardiovascular system, nicotine being a sympatheticmimetic substance, it promotes the release of catecholamines, epinephrine and norepinephrine, activated by the sympathetic nervous system. This activation of the sympathetic nervous system is responsible for increased heart rate (HR) and systolic blood pressure (SBP) and diastolic blood pressure (DBP). The study aims to understand whether tobacco consumption has an acute impact on BP and HR values. Material and methods: The present study was observational, cross-sectional and analytical. The sample consisted of 28 young adults, of both sexes, between 18 and 30 years of age. BP and HR were evaluated using the diagnostic examination of ambulatory blood pressure monitoring, Welch Allyn ABPM6100. BP and HR were evaluated before, during and after smoking. Results: There was a significant increase in SBP, DBP and HR values during smoking in both cigarettes, with maximum mean values (1st cigarette: SBP 133.21 mmHg, DBP 81.57 mmHg and HR 98.93 bpm; 2nd cigarette: SBP 132.82 mmHg, DBP 78.89 mmHg and HR 92.46 bpm). After smoking, there was a significant decrease in BP and HR at 15 minutes of recovery, with minimum mean values in the 3rd evaluation (1st cigarette: SBP 126.43 mmHg, DBP 75.79 mmHg and HR 83.82 bpm; 2nd cigarette: SBP 126.43 mmHg, DBP 76.14 mmHg and HR 83.79 bpm). Regarding the values referring to the moment before smoking each cigarette, it was observed that SBP, DBP were higher in the 2nd cigarette compared to the 1st cigarette. Discussion: During the act of smoking, in both cigarettes, there were significant differences for SBP, DBP and HR, when compared the moment before smoking with the 1st evaluation at the time of smoking. The nicotine present in cigarettes promotes the release of neurotransmitters, norepinephrine, and epinephrine, activated by the sympathetic nervous system, being responsible for the increase in BP and HR. Conclusion: The beginning of smoking is associated with an increase in BP and HR values, decreasing after smoking.